Towards the Designation of Amazons : [Etymological study] - Inga Sanikidze (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
I think that a trace of the Georgian language is seen in the “amazon” stem which supported by several arguments worth mentioning; in particular, Appian’s evidence on “warrior women being called Amazons by local barbarians”, which indicates the non-Greek origin of this name. Simultaneously, in the nominal stem we have to distinguish the Chan –on affix which diachronically had the functions of expressing possessing and multiplicity of similar subjects. According to Herodotus, the Scythian designation “Oiorpata” of the Amazons appears to be a word of complex composition and it is translated into Greek as “people killers”, of these “oior” meant a “man” (//brave) and “pata” “killing, to kill” [Herodotus]. In my opinion, the first segment of the Scythian complex stem must be calque which may have appeared in the Scythian language through the influence of the Georgian languages. Hence, I think that by its origin is the lexeme “amazon-[i] Kartvelian and in it the prepositional “m” consonant, could have got lost because of lack of knowledge of the semantic meaning of the word in the Greek-speaking world; i.e. the Georgian *mamats-on-[i] in the Greek language would give us the versions amats-on-amaz-on//amadz-on; It follows that the word means nothing anything else but a group of brave men (here of brave women), their army.